(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2017)
The objective of this research was to identify the thinking styles of students in the Psychology and Society research group at the University of Pamplona, through a mixed study using a non-probabilistic sample of 10 students belonging to the academic community. The Sternberg and Wagner Inventory (1992), a semi-structured interview, and an observation format were applied. The results establish the prevalence of Hierarchical (83.54%), Legislative (81.01%), Liberal (72.15%), Executive (63.29%), Judicial, and Local (62.03%) styles, which are characterized by goal prioritization, innovation, independence, and teacher support.